Social Trust and Central-Bank Independence - Niclas Berggren; Sven-Olof Daunfeldt; Jörgen Hellström (Research Institute of Industrial Economics (IFN), 2012)
Central banks have been made more independent in many countries. A common rationale has been the existence of a credibility (or lack-of-trust) problem for monetary policy. This indicates a possible and until now unexplored link between social trust and central-bank independence. Our empirical findings, based on data from 149 countries, confirm that there is such a link, in the form of a u-shaped relationship. We suggest that two factors help explain this finding: the need for this kind of reform and the ability with which it can be implemented. At low trust levels, the need for central-bank independence is strong enough to dominate the low ability; at high trust levels the ability for reform is high and dominates the low need; at intermediate trust levels there is neither need nor ability strong enough to generate very independent central banks.
Keywords: E52; E58; P48; Z13; 330; Trust; Credibility; Reforms; Monetary Policy; Inflation; Central Bank; Time Inconsistency; Vertrauen; Glaubwürdigkeit; Geldpolitik; Zentralbankunabhängigkeit; Regression; Welt